Facilitation and plant phenotypic evolution - Verdú, M.; Gómez, J.M.; Valiente-Banuet, A.; Schöb, C. (Trends in plant science, 2021)
While antagonistic interactions between plants have been a major topic of eco-evolutionary research, little evidence exists on the evolution of positive plant interactions (i.e., plant facilitation). Here, we first summarize the existing empirical evidence on the role of facilitation as a selection pressure on plants. Then, we develop a theoretical eco-evolutionary framework based on fitness-trait functions and interaction effectiveness that provides predictions for how facilitation-related traits may evolve. As evolution may act at levels beyond the individual (such as groups or species), we discuss the subject of the units of evolutionary selection through facilitation. Finally, we use the proposed formal evolutionary framework for facilitation to identify areas of future research based on the knowledge gaps detected. Plant facilitation is a crucial interaction shaping past and present communities, but its evolutionary potential as a selective force is currently unknown.An evolutionary framework based on fitness-trait functions and the effectiveness of the interaction provides clear predictions about the evolution of facilitation traits.The evolutionary potential of facilitation may go beyond the individual and act at different levels (groups and species).